Motivación y autoeficacia en mujeres que estudian carreras de perfil informático - Bastos, Marcela S. (2017)
This paper presents a motivational methodology to increase the participation of women in programming contests. The impact of this methodology is show in different activities developed by the students participating of these contests, in a research group of a public institution and between students of a private university. The work systematics turns out the selfefficacy of the woman in a area where the male prejudice still prevails.